2010
DOI: 10.4103/0973-3930.62599
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of gestational diabetes mellitus: A case control study in a district tertiary care hospital in south India

Abstract: Objective:To study the determinants of Gestational Diabetes Mellitus (GDM).Design:Case-control study. Setting: Sri Avittom Thirunal Hospital, Thiruvananthapuram district, Kerala, South India.Participants:300 GDM women as cases and 300 age-matched controls.Study variables:Sociodemographic characteristics, pre-pregnancy Body Mass Index (BMI), menstrual history, obstetric history, infertility history, family history of diabetes in first degree relatives, recurrent urinary tract infection (UTI), and moniliasis.Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 17 publications
6
21
2
Order By: Relevance
“… 10 , 34 Family history of diabetes was concluded in several cross sectional and prospective studies as a highly significant risk for developing GDM. 35 , 36 Wang et al found that 54.9% of the incidence of GDM was significantly found among pregnant women with PCOS compared to 14.3% of those in the control group. 18 Therefore, recognizing such risk factors among pregnant women in Yemen is important and should be done by the medical staff in order to prevent the adverse effects of GDM.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 34 Family history of diabetes was concluded in several cross sectional and prospective studies as a highly significant risk for developing GDM. 35 , 36 Wang et al found that 54.9% of the incidence of GDM was significantly found among pregnant women with PCOS compared to 14.3% of those in the control group. 18 Therefore, recognizing such risk factors among pregnant women in Yemen is important and should be done by the medical staff in order to prevent the adverse effects of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported various risk factors associated with higher rates of GDM, mainly focused on traditional risk factors such as age, BMI etc. [ 12 ; 15 – 17 ; 21 24 ], but much remains to be understood particularly about socio-economic factors behind the high rates of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 14 15 ] In the setting of high prevalence of type 2 diabetes, these women also are prone to have a positive family history which also adds to the risk of gestational diabetes. [ 13 ] It is inevitable for the state's health system to be equipped to face the consequences of the burgeoning burden of gestational diabetes in the near future. Understanding the various outcomes of gestational diabetes would be the key to initiate the cascade of preparatory steps to tackle them.…”
Section: Introductionmentioning
confidence: 99%